Metode Pembelajaran Berbasis Bermain pada Anak Usia Dini di TK/MI YASPA Palembang - Ramadhanti, Safira Dwi; Mawardah, Mutia (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
Early childhood refers to children aged 0–8 years who are in a stage of physical and mental growth and development. One effective way for children to learn during this period is through play. Learning while playing can be enjoyable and engaging for children. The approach that combines play and learning integrates playful activities into the teaching and learning process, aiming to create a joyful atmosphere and encourage active participation. Community-based research indicates that play-based learning methods are highly effective in enhancing young children’s abilities. This approach not only supports cognitive development but also strengthens social, emotional, and physical aspects. Early childhood education serves as a fundamental stage in shaping children’s abilities and character for the future. During this phase, children experience rapid growth and development, both physically and psychologically; therefore, the learning approach should be designed appropriately and responsively to meet their developmental needs.